1985
DOI: 10.1002/tcm.1770050103
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute maternal toxicity on fetal development in the mouse

Abstract: The effects of acute alterations in maternal health status upon fetal development were assessed following exposure of pregnant CD-1 mice on day 8 of gestation to one of ten chemicals at doses calculated to exert either a low or a moderate degree of maternal lethality. The dams were killed on day 18 of gestation, and the fetuses were examined by routine teratological techniques. The chemicals were cacodylic acid, caffeine, deltamethrin, dinoseb, ethylene bisisothiocyanate sulfide (EBIS), endrin, guthion, kepone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 10 publications
(4 reference statements)
2
58
1
2
Order By: Relevance
“…These data seem to suggest a correlation between the severity of maternal toxicity and the effects on the conceptuses, however a definite relationship cannot be extrapolated because the concurrent role of the test compound in inducing the effects must be taken into account. The role of maternal toxicity in the induction of adverse effects on conceptuses is a very long standing problem that has been faced by a number of researchers (Chahoud et al, 1999;Chernoff et al, 1989;ECETOC, 2004;Kavlock et al, 1985;Khera, 1984Khera, , 1985Paumgartten, 2010;Rogers et al, 2005), apparently without a definite solution. First of all the definition of maternal toxicity is very poor.…”
Section: Introductionmentioning
confidence: 99%
“…These data seem to suggest a correlation between the severity of maternal toxicity and the effects on the conceptuses, however a definite relationship cannot be extrapolated because the concurrent role of the test compound in inducing the effects must be taken into account. The role of maternal toxicity in the induction of adverse effects on conceptuses is a very long standing problem that has been faced by a number of researchers (Chahoud et al, 1999;Chernoff et al, 1989;ECETOC, 2004;Kavlock et al, 1985;Khera, 1984Khera, , 1985Paumgartten, 2010;Rogers et al, 2005), apparently without a definite solution. First of all the definition of maternal toxicity is very poor.…”
Section: Introductionmentioning
confidence: 99%
“…Kavlock et al (1985) found a similar increase in supernumerary ribs with DMA V treatment in mice after maternal exposure on GD 8, and correlated these to the treatment-related retardation of maternal weight gain. In the rats at the lower DMA V dose levels, there were statistically significant intergroup differences in the incidences of some fetal skeletal variants but, due to lack of dose-relationship, none was considered indicative of a treatment effect.…”
Section: Dma Vmentioning
confidence: 60%
“…The authors found the latter effect to be correlated with the magnitude of the effect on maternal weight gain. The results reported by Kavlock et al (1985) are inappropriate for evaluating the risks of developmental effects in humans because (1) clearly maternally toxic, sometimes lethal doses were used, and (2) the numbers of dosage groups were not sufficient to enable evaluation of the dose-response relationship for DMA V (DeSesso et al, 1998;Jacobson et al, 1999;Holson et al, 2000). In a later study, Chernoff et al (1990) assessed a group of 16 pregnant Sprague-Dawley rats at term after oral administration of 40 mg/kg/day DMA V once daily during organogenesis (GD 6-15).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…An increased incidence of supernumerary ribs was observed in both dinoseb-treated groups. The authors noted that increased incidence of supernumerary ribs may be a response to a non-specific disruption in maternal status (Kavlock et al, 1985). Administration of dinoseb to pregnant CD-1 mice by gavage on GDs 7-8 at 50 mg/kg bw/day in NaOH produced reduced fetal weight and increased incidence of fetuses with supernumerary ribs (71% in litters) without maternal death.…”
Section: Gavage Studies In Micementioning
confidence: 99%